Social studies teachers’ feedback experiences: A phenomenological study - Özalp, M. Talha; Kaymakcı, Selahattin (Nevsehir Haci Bektas Veli Universitesi SBE Dergisi, 2025)
This study aims to explore social studies teachers’ experiences regarding the use of feedback in social studies education. The research was designed in line with the phenomenological approach, qualitative research designs. The study group consists of 18 social studies teachers with varying levels of professional seniority, working across Turkey’s seven geographical regions. Data were collected through semi-structured interviews and analyzed using content analysis. Findings indicate that teachers predominantly defined feedback in terms of response, correction, and reinforcement, revealing notable conceptual ambiguities. Most participants had not received any formal training on feedback, although they expressed a desire to do so. Teachers most frequently used positive and corrective types of feedback and perceived effective feedback as timely and tailored to individual students. Challenges identified included time constraints, overcrowded classrooms, and a limited student engagement. This study makes a unique contribution by examining social studies teachers’ feedback experiences from a multidimensional perspective and raising awareness of teachers’ classroom practices.